Biochar Amendment On Palm Oil Biomass Effect On Physicochemical Properties And Fibre Degradation - Gusman, Muhammad Hashim Habibie Arif (Universiti Sains Malaysia, 2021)
Empty fruit bunch has a complex structure that difficult to break during the composting process due to the high lignocellulose content that consists of hemicellulose, cellulose, and lignin. The objective of this study was to examine the effect of biochar in physicochemical changes in empty fruit bunch (EFB) composting and determine the degradation of Lignin, Cellulose, and Hemicellulose of empty fruit bunch fibre during the composting process. The composting sample was consist of EFB only, EFB +POME and EFB+POME+Biochar.The mixture of EFB:POME: Biochar was prepared in the ratio of 10:1:5 respectively. There are several parameters that need to measure that consist of pH, electric conductivity (EC), moisture content, volatile solid (VS), Carbon and Nitrogen ratio (C/N), total Phosphorus and fibre to observe the behaviour of composting process of empty fruit bunch. This parameter was examined in an environmental laboratory that complete with pH meter, YSI meter for electric conductivity, laboratory oven and Furnance 550°C. The overall result for EFB, EFB +POME and EFB+POME+Biochar composting trend is quietly similar in pH, volatile solid, moisture content, total phosphorus and C/N ratio. Electric conductivity and fibre show different profiles due to the different characteristics of composting with biochar and without biochar. Moreover, the composting rate in presence of biochar produces rapid compost due to it characteristic such as large porosity, large surface area and favoring the microbial growth that increases the microbial activity. The presence of biochar in the composting process can produce effective compost and reduce the consuming time to stabilize the EFB product during composting process.